The need for cycloplegic refraction in adolescents and young adults - Hagen, Lene A.; Gilson, Stuart J.; Baraas, Rigmor C. (Scandinavian Journal of Optometry and Visual Science, 2023)
Cycloplegic refraction is considered the gold standard method when examining children and for ensuring accurate refractive error assessment within epidemiological studies. Recent reports underline that cycloplegia is equally important for ensuring accurate refractive error assessment in Chinese adolescents and young adults (Sun et al., 2018). The aim of this study was to assess whether cycloplegia is of equal importance for refractive error assessment in Norwegian adolescents and young adults. Non-cycloplegic and cycloplegic autorefraction (Huvitz HRK-8000A), and cycloplegic ocular biometry (IOLMaster 700), were undertaken in 215 Norwegian adolescents (101 males) aged 16–17 years. Topical cyclopentolate hydrochloride 1% was used for cycloplegia. Two years later, autorefraction and ocular biometry were repeated in 93 of the participants (34 males), both non-cycloplegic and cycloplegic. Non-cycloplegic spherical equivalent refractive errors (SER = sphere + 1⁄2 cylinder) were more myopic (less hyperopic) than cycloplegic SER in 93.6% of the participants (overall mean ±SD difference in SER: -0.59 ±0.50 D, 95% limit of agreement: -1.58 – 0.39 D). Refractive error classification by non-cycloplegic SER underestimated the hyperopia frequency (10.4% vs. 41.4%; SER ≥ +0.75 D) and overestimated the myopia frequency (12.1% vs. 10.7%; SER ≤ -0.75 D), as compared with refractive error classification by cycloplegic SER. Mean crystalline lens thickness decreased and mean anterior chamber depth increased with cycloplegia, with the largest changes in the hyperopes compared with the emmetropes and myopes (p ≤ 0.04). The individual differences between non-cycloplegic and cycloplegic SER varied by more than ±0.25 D between first and second visit for 31% of the participants. Accurate baseline measurements — as well as follow-up measurements — are imperative for deciding when and what to prescribe for myopic and hyperopic children, adolescents, and young adults. The results here confirm that cycloplegia is necessary to ensure accurate measurement of refractive errors in Norwegian adolescents and young adults.